Manufacturing competitive priorities and weaknesses of Slovenian companies: An empirical investigation - Borut Rusjan (Journal for East European Management Studies, 2000)
This Article examines several research questions relative to the content of manufacturing strategy on the basis of empirical data gathered on a sample of Slovenian manufacturing firms: What were the most important manufacturing competitive priorities of sampled Slovenian companies in the past and what changes in manufacturing competitive priorities are predicted for the future? What systems, policies, practices in production are prevalent in sampled Slovenian firms? What are the most important manufacturing weaknesses that determine the most important strategic decision areas in production in the future? Descriptive statistic has been used to describe the current industry practice and explore characteristics of manufacturing strategy of Slovenian firms. – – In diesem Artikel werden auf der Basis empirischer Daten einige Fragestellungen in Bezug auf die Fertigungsstrategien in slowenischen Unternehmen untersucht: Welches waren die höchsten Wettbewerbsprioritäten in der Vergangenheit und welche Veränderungen werden in der Zukunft erwartet? Welche Systeme und Richtlinien sind in den untersuchten slowenischen Unternehmen vertreten? Welches sind die größten Schwächen im Herstellungsprozeß und worin bestehen die damit verbundenen strategischen Entscheidungen für die Zukunft? Unter Einsatz deskriptiver Statistik wird die aktuelle Lage beschrieben, und wichtige Charakteristika der Produktionsstrategie slowenischer Unternehmen werden dargestellt.
Keywords: 650